(untitled) (Journal of Educational Sciences, 2016)
In the article the authors of the article considers the technology of designing the content of professional preparation of a social pedagogue through the disclosure of the contents of the elective course "the Contents of preparation of a social pedagogue: competence-based approach". Elective course has been prepared for students of the speciality 5В012300 – "Social pedagogic and self- cognition". This course has been prepared in the form of teaching-and-methodical complex of discipline in accordance with the educational plan of speciality, as well as on the basis of a study of master of modern achievements of social and pedagogical science. The research was conducted under the guidance of a supervisor. The purpose of course is formation of system of knowledge, result oriented, and knowledge of the competence approach. The future social teachers also in the framework of the course should master their future professional competence. In the course of the study programme this course, the authors tried to focus the attention of prospective students on the understanding and design of the trajectory and structure of knowledge, recommended that the scientific literature of the modern level of development of the methodology of socio-pedagogical work. Didactic principles of designing of the educational program of the course «the principle of science, communication theory with practice, succession, a systematic and others. The methodical principles of design – personal orientation, компетеностного approach, the importance of self-reliance, self-consciousness and self-organization of training of students and another. The content of the course was экспертировано practitioner’s social workers. The experts particularly emphasized the necessity of formation of communicative комптенции have a social pedagogue, the ability to interact with the pupils ’ parents, to search for ways of social assistance and social support to low-income families and children. The structure of this article includes: introduction, «the Contents of preparation of a social pedagogue», «Practice of the expert poll social pedagogues» the conclusion.